Simulasi PHET: Efektivitasnya terhadap pemahaman konsep bentuk molekul - Aulia Nurul Aziza; Dedi Irwandi; Evi Sapinatul Bahriah (Hydrogen: Jurnal Kependidikan Kimia, 2021)
Students have problems in understanding Students have problems in understanding of Molecule Shapes Theory, this can be caused by the lack of visualization of the spatial structure of molecules. So that requires teachers to be creative and innovative, for example by utilizing technology-based learning media. One of the technology-based media that can be used to deliver molecular form material is the PhET simulation media. The purpose of this research is to see the effectiveness of PhET simulation media on mastering the concept of molecular shapes. The research method used was quasi-experimental. The research design used was nonequivalent control group design. The sample in this study were students of class X IPA 1 totaling 39 students and X IPA 2 totaling 40 students. The research instrument used was a multiple choice test to see student learning outcomes and a questionnaire to determine student responses to the use of PhET media. Data were analyzed using SPSS version 25. Research results from the Independent Sample T-Test hypothesis test showed that learning using the PhET simulation media in the experimental class was more effective in improving students' understanding of concepts in molecular form material compared to book media.